Heparin-induced thrombocytopenia - Warkentin, Theodore E., 1960-; Greinacher, Andreas, (Fundamental and clinical cardiology series (unnumbered), 2013)
Suitable for clinicians and hematology consultants, this title includes: coverage of approved and novel pharmacotherapies, dosing guidelines, and the advantages and limitations of alternative anticoagulants; review of the immune basis and pathogenesis, animal models, and laboratory testing for HIT antibodies; and more.